Inhibition of interleukin-8 reduces tumorigenesis of human non-small cell lung cancer in SCID mice. - Arenberg, D A (1996)
The salient feature of solid tumor growth is the strict dependence on local angiogenesis. We have previously demonstrated that IL-8 is an angiogenic factor present in freshly isolated specimens of human non-small cell lung cancer (NSCLC). Using a model of human NSCLC tumorigenesis in SCID mice, we now report that IL-8 acts as a promoter of human NSCLC tumor growth through its angiogenic properties. Passive immunization with neutralizing antibodies to IL-8 resulted in more than 40% reduction in tumor size and was associated with a decline in tumor-associated vascular density and angiogenic activity. IL-8 did not act as an autocrine growth factor for NSCLC proliferation. The reduction in primary tumor size in response to neutralizing antibodies to IL-8 was also accompanied by a trend toward a decrease in spontaneous metastasis to the lung. These data support the notion that IL-8 plays a significant role in mediating angiogenic activity during tumorigenesis of human NSCLC, thereby offering a potential target for immunotherapy against solid tumors.